An Efficient Post-Quantum Secure Two-Tier Signature Scheme Based on Chameleon Hashing (Contemporary Mathematics, 2025)
In light of the growing threat from quantum adversaries to traditional digital signatures, the paper investigates a post quantum secure signature scheme integrates chameleon hash functions within a two-tier signing framework. The proposed construction achieves essential security features such as non-repudiation and recipient-specific verification, while maintaining a non-interactive structure compatible with efficient hash-and-sign paradigms. A novel enhancement of the Kabatianskii-Krouk-Smeets (KKS) code-based scheme is incorporated, leveraging rank metric techniques over large finite fields to bolster resistance against both classical and quantum attacks. The layered architecture, separating long-term and ephemeral keys, supports multi-message authentication and improved key lifecycle management. Comprehensive security definitions and reductions are provided to demonstrate the scheme’s unforgeability under realistic assumptions, establishing its viability for robust post-quantum applications.
Keywords: code-based signatures; chameleon hashing; two-tier cryptographic frameworks; rank metric security